Feeling safe, feeling connected: aesthetic and polyvagal approaches to dementia care - Fox, Sarah; Davies, Jennie; Dowlen, Robyn; Keady, John; Thompson, James; Watson, Ruth (Frontiers in Dementia, 2026)
This perspective brings together authors from care aesthetics, dementia studies, mental health nursing, and clinical psychology to explore how aesthetics and Polyvagal Theory intersect in dementia care. Across these fields, there is growing recognition that wellbeing is shaped not only by clinical interventions but also by the subtle, embodied cues that create a sense of safety, connection, and belonging for patients. Concepts such as aesthetic care, in-the-moment practices, and everyday aesthetics emphasize how lived experience and wellbeing is grounded in the sensory and relational details of everyday life. In parallel, Polyvagal Theory provides a psychophysiological framework for understanding how people respond to such cues through the process of threat detection, co-regulation, and social engagement. By placing these perspectives side-by-side, we explore the currently untapped benefits of developing a cross disciplinary therapeutic toolkit for clinicians working with people living with dementia. Looking ahead, integrating aesthetics and Polyvagal-informed approaches could reshape dementia care into a practice that values safety, connection, and meaning as core clinical outcomes. Although further research is needed to translate this integrated model into practice, the work of the authorship in both research and clinical practice with people with dementia illustrate that such approaches are already ongoing and can bring tangible benefits for several stakeholders, including people living with dementia.